2022
DOI: 10.3390/met12122056
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis and Validation of Segments C2-C7 of the Cervical Spine

Abstract: As an important part of the human spine, the cervical spine has a complex structure and easily suffers from diseases. Analysis of the biomechanical mechanism of cervical spine structure using the finite element model is not only helpful for the diagnosis, treatment and prevention of cervical spine diseases but also has positive significance for the performance evaluation of cervical spine implants. In this paper, a method of establishing a cervical C2-C7 finite element model based on CT image data is studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The numerical simulations and mechanical experiments were carried out to characterize the equivalence between the designed fixture and the natural cervical sections, and the results indicated that this novel biomimetic fixture could reflect the biomechanical characters of the natural human cervical vertebrae with acceptable accuracy. In another work by Cheng et al [3], a C2-C7 3D finite element model of the cervical spine was constructed based on the data from cervical CT images. Different pure moment loads were used to simulate flexion/extension and the relative motion range between vertebral bodies.…”
Section: Contributionsmentioning
confidence: 99%
“…The numerical simulations and mechanical experiments were carried out to characterize the equivalence between the designed fixture and the natural cervical sections, and the results indicated that this novel biomimetic fixture could reflect the biomechanical characters of the natural human cervical vertebrae with acceptable accuracy. In another work by Cheng et al [3], a C2-C7 3D finite element model of the cervical spine was constructed based on the data from cervical CT images. Different pure moment loads were used to simulate flexion/extension and the relative motion range between vertebral bodies.…”
Section: Contributionsmentioning
confidence: 99%
“…The geometric models of the fatigue-testing fixture with DCI and the cervical bodies with DCI were established, which were input into the finite element analysis software ANSYS Workbench 16.0 (Ansys, Canonsburg, PA, USA) and assigned with corresponding material properties, as shown in Table 1 [25,26]. In the numerical calculation of the equivalent stress and deformation of DCI within the C5-C6 cervical spinal segments during the static test, the maximum routine loading parameters in biomechanical tests with cervical spines from cadaver donors were followed; namely, a 73.6 N preload was applied to the top surface of C5, with an extra 1.8 Nm flexion moment for flexion movement and a 1.8 Nm extension moment for extension or a 1.0 Nm lateral bending moment for bending, respectively, while the bottom surface of C6 was fixed in six degrees of freedom in the finite element model [26][27][28].…”
Section: Functional Bionics Of Fatigue-testing Fixturementioning
confidence: 99%